Key features of the first phase of the national cluster program in Russia - Evgeniy Kutsenko; Dirk Meissner (European Regional Science Association (ERSA), 2013)
In recent years, Russian federal authorities have started moving from drafting of strategies, concepts and guidelines related to cluster development, to formation and implementation of cluster programs. The major initiative on this way was the selection of the pilot innovative clusters announced on March 19, 2012 by the Ministry of Economic Development of the Russian Federation. In total, there were submitted 94 cluster projects. In the first stage the projects were evaluated by the wide group of experts. Further, the selected clusters (in number of 37) presented their programs at the meeting of ?the Working Group for the Development of Public-Private Partnership in the Innovation Sphere?. Among the 37 clusters 5 submitted in the field of nuclear technology, 4 ? in aerospace and aviation, 9 ? in biotechnology, pharmaceutics, medical devices, 4 ? in information and telecommunication technology, 3 ? in novel materials, 3 ? in machinery, 5 ? in lightening and electrical equipment and instruments 4 ? in chemical products. Finally It was selected 25 pilot clusters, which is planned to be provided with comprehensive government support. The presentation consists of three part: ? Policy background of national cluster program 2012 ? Key features and results of the selection process ? A preliminary comparison of Russian cluster program with widely known EU cluster programs (BioRegio, InnoRegio, Competitiveness poles, etc) In my presentation I?m going to lighten the most essential elements of the forming cluster program in Russia: ? characteristics of the supported object, ? criteria for selection of the pilot clusters, ? selection procedure, ? description of the selected pilot clusters, ? budget, directions and supporting mechanisms for pilot clusters, ? monitoring of the implementation of cluster supporting programs. In addition, I will be addressing the key features of the Russian cluster program in comparison with the most famous European programs: BioRegio, InnoRegio (German), Competitiveness clusters (France). I have found several similar features and among them: * Russian cluster program is a cooperation-contest one; * complex inter-governmental co-ordination; * the volume of support is consistent with the similar programs; * first-priority support from other instruments of innovation development; * significant share of applications that are not granted. And also there are differences and some of them are essential: * in many cases there is a significant lack of private initiatives; * there is no emphasis on SME, start-ups, growth of new companies growth; * different principles of support; * for the Russian program, questions of monitoring and evaluation haven?t been discussed yet. At the end of my presentation I?m going to highlight and discuss the rooms for improvement of Russia cluster policy.
Keywords: 330; cluster; cluster policy; innovation; innovation policy